Taxation Policy by Tax Incentive For Foreign Investment in Timor Leste - Carlos Afonso BARRETO (International Journal of Environmental, Sustainability, and Social Science, 2020)
The Foreign Investment Law, namely Law Number 5 Year 2005 Articles 14 and 15 concerning the granting of tax incentives to entrepreneurs, especially foreign investors. The Timor Leste government has prepared tax incentives to increase the value of investment to foreign investors. This research is a qualitative study. Methods of data collection using observations and structured interviews. Meanwhile, the data used are taxation reports, taxation policies on investment incentives and foreign investment. The research was carried out on the officials of the Director General of Tax and Customs of Timor Leste, the Head of the Foreign Investment Board of Timor Leste, the Head of Fiscal Policy are several Timorese and a National Director in Tax and Customs of Timor Leste and staff. The result of the research states that tax revenue will decrease with the tax incentives, but after investment activities run smoothly, investors will become taxpayers. The government must prepare itself both in terms of infrastructure, human resources, government administration bureaucracy to host foreign investors.